Host range and virulence of Metarhizium pingshaense against Chilo species and expression of fungal virulence genes in Conogethes punctiferalis - C. M. Senthil Kumar; M. Samyuktha; M. Balaji Rajkumar; M. Punithavalli; Sharon D’Silva; C. Geethu; P. Ahalya; T. K. Jacob; S. Devasahayam; A. I. Bhat (Scientific Reports)
Abstract The infectivity and virulence of Metarhizium pingshaense was tested against three major pests: Chilo infuscatellus (sugarcane early shoot borer), C. sacchariphagus indicus (sugarcane internode borer) and C. partellus (sorghum stem borer). Bioassay studies indicated high pathogenicity of this fungus against all the three species with the highest mortality recorded in C. sacchariphagus indicus (96%), followed by C. infuscatellus (93%) and C. partellus (83%). The median lethal concentrations of M. pingshaense against late-instar larvae were 4.6 × 105, 1.7 × 105, and 9.5 × 105 conidia/ml for C. infuscatellus, C. sacchariphagus indicus, and C. partellus, respectively. Median survival times ranged from 5.3 to 6.9 days for C. infuscatellus, from 5.4 to 7.9 days for C. sacchariphagus indicus, and from 6.9 to 8.3 days for C. partellus, at the tested doses of 1 × 10⁸ and 1 × 10⁷ conidia/ml. Qualitative and quantitative analyses of cuticle-degrading enzymes by the fungus, which are critical virulence factors, confirmed the production of chitinases and lipases. Enzyme production significantly increased in media with insect cuticle, indicating substrate-dependent regulation. Genes encoding chitinase and protease were cloned, sequenced, and were found to be closely related to those of M. anisopliae. RT-PCR studies confirmed the temporal expression of these two virulence genes, which play a critical role in pathogenesis. There was a gradual upregulation of these genes in the fungus during infection of its original host, Conogethes punctiferalis with the progression of time rising up to 3000-fold compared to untreated insects. These findings highlight the potential of M. pingshaense as an effective biocontrol agent for a wide range of crambid pests, supporting its development as a broad-spectrum mycoinsecticide.